Romania : Financial System Stability Assessment, Including Reports on the Observance of Standards and Codes on the following topics; Banking Supervision, Securities Regulation, Anti-Money Laundering and Combating the Financing of Terrorism, Monetary and Financial Policy Transparency. (IMF Staff Country Reports; Country Report ;, 2003)
The program of budget restraint and reduction of the quasi-fiscal losses, supported by the IMF's Stand-By Arrangement, was successful in bringing domestic demand down to sustainable levels, lowering inflation, and narrowing the current account deficit. The stabilization effort was supported by the fiscal policy. A sensitivity analysis is used to assess banking sector vulnerabilities. The Deposit Guarantee Fund (DGF) is operating satisfactorily but will need to strengthen its resources considerably to provide a sufficient level of support. The insurance sector is small and underdeveloped.